"Sinus headache": rhinogenic headache or migraine? An evidence‐based guide to diagnosis and treatment. Issue 3 (5th November 2012) - Patel, Zara M.; Kennedy, David W.; Setzen, Michael; Poetker, David M.; DelGaudio, John M.
<x xml:space="preserve">Abstract</x> Background Patients present to physicians across multiple disciplines with the complaint of sinus headache. This lay term is widely accepted in the media, yet has been repeatedly questioned in the medical literature, and experts in the fields of otolaryngology, neurology, and allergy have agreed that it is an overused and often incorrect diagnosis in the majority of patients. There have been review articles and consensus panels established regarding this issue, but thus far no guidelines based purely on a review of the level of evidence provided by the literature. Methods A systematic review of the literature was performed and the Clinical Practice Guideline Manual, Conference on Guideline Standardization (COGS), and the Appraisal of Guidelines and Research Evaluation (AGREE) instrument recommendations were followed. Study inclusion criteria were: adult population >18 years old, self‐diagnosed or physician‐diagnosed "sinus headache, " clearly defined diagnostic criteria in diagnostic studies, and clearly defined primary clinical end‐point in therapeutic studies. Results We identified and evaluated the literature on diagnosing and treating patients with a primary complaint of sinus headache. The literature was reviewed for both quality of research design as well as benefit and harm of the proposed interventions. Conclusion If a thorough neurologic and otolaryngologic evaluation is performed, the majority of patients presenting with sinus headache in the absence of significant acute inflammatory findings will be diagnosed with migraine. In this situation, the appropriate treatment for the majority of patients presenting with sinus headache is migraine directed therapy. In a highly select group of patients, directed nasal surgery addressing endonasal contact points may be an option.